Flexibilité et intentionnalité dans la communication gestuelle chez les grands singes - Catherine Hobaiter (Revue de Primatologie, 2014)
The gestural communication of great apes is a rich and complex system. It is used in a flexible manner with the intention to communicate specific goals to specific individuals - as such, it shares many of the basic attributes of human language, supporting the idea that the two systems share a common evolutionary root. Significant advances in the subject were made through longitudinal studies of gestural communication in captive apes and, more recently, the systematic study of wild apes. We evaluate the current literature and discuss the evidence for common features in human language and great ape gesturing. The predominantly ‘species-typical’ nature of the gestural repertoire does not refute the clear evidence of its use in intentional communication, but raises intriguing questions about the degree of intentional signalling that may have been overlooked in other systems of communication.